‘Turning Job Seekers to Job Creators’: Talent Management Module Development for TVET Graduates - Abdul Wafi, Anisah; Subri, Ummu Sakinah; Asshaari, Izamarlina; Mohd Zulkifli, Rafeizah; Mohamed, Suriani; Che’ Rus, Ridzwan (Journal of Technical Education and Training, 2023)
The COVID-19 pandemic negatively impacted the economy, particularly the downsizing of operations and retrenchment, which affected various sectors. Post-pandemic prompted a shift in the perspective; rather than waiting for jobs, it seems that individuals needed to become job creators. In this regard, the Technical and Vocational Education and Training (TVET) is believed to be a prominent field of study that could facilitate graduates to become job creators. Nevertheless, some of graduates would not consider owning businesses after graduation, indicating the difficulty of becoming job creators. Therefore, this study emphasising TVET program built and validated a Talent Management Module (MTM) involving creation (Job Creator) based on the Cognitive Information Processing (CIP) theory. It comprised both quantitative and qualitative phases. First, a series of interviews were carried out to explore the perceptions of talent management (TM) among seven experts. Second, a quantitative study involving data interpretation analysis based on the validity of the module content was obtained using the interview technique. Third, the module content validation process involved seven experts comprising academics and Malaysian career academy entrepreneurs whose backgrounds included entrepreneurship and TVET. The results showed that nine variables were involved, namely 1) Communication, 2) Critical Thinking and Problem-Solving Skills, 3) Teamwork Skills, 4) Continuous Learning and Information Management, 5) Entrepreneurial Skills, 6) Leadership Skills, 7) Professional Ethics and Moral, 8) Career Adaptability, and 9) Digital technology. Overall, MTM that was built in this study was consented to by the appointed experts. The development of this module might better be considered to encourage graduates to create prospective job creation that could reduce the unemployment rate. Therefore, the proposed MTM might be an appropriate solution to address unemployment through the identified important components in the implementation and empowerment of career programmes across TVET graduates.